Thought Processes Among Teachers Teaching Specific Subjects in Secondary Schools - Osman, Rosma (2004)
This research seeks to study thought processes among teachers teaching specific subjects in secondary schools. The research design was a descriptive correlational study and the data were collected using mailed questionnaires. The study employed the survey method. A stratified sampling technique was used to select 400 teachers. A response rate of 71.75% (287) was considered to be acceptable. Both the descriptive and inferential statistics were used to analyse the data. The research finding showed that two-thirds of the teachers' thought processes was low. Almost one-third of the teachers were at the intermediate-level and a very minimal percentage was high-level. There was no significant difference between regular and residential school teachers' thought processes. The result also suggested that the mean of Science and Mathematics teachers' thought processes scored significantly higher than Bahasa Melayu and Bahasa Inggeris teachers in their level of thought processes. However, teachers' professional qualification did not show any significant difference. With the exception of teachers' critical thinking disposition and teachers' concern, all the other variables did not correlate significantly with teachers' thought processes. Multiple Regression Analysis showed that the significant predictors for teachers' thought processes in curriculum instruction are critical thinking disposition and teachers' concern. Based on the fmdings of the study, two new variables for educational change were proposed. The study mainly recommended that policymakers should fmd means to improve teachers' level of commitment and emphasize moral purpose explicitly into the instructional objectives. This is because even if all the relevant factors for successful educational change are taken care of, the intended outcome will fail to occur if teachers are not committed and did not see that the change has professional value to them. Finally, other recommendations for practice and future research were put forward.